ANALYSIS OF THE EFFECT OF PRODUCT QUALITY,PROMOTION, PRICE ON CONSUMER LOYALTY THROUGH SATISFACTION AS AN INTERVENING VARIABLE IN FORTUNE COOKING OIL (Case Study : Housewife in Lubuklinggau Utara II Sub-District) - Nopriani, Melly; Nabiu, Musriyadi; Priyono, Basuki SIgit (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
According to the Lubuklinggau City Industry and Trade Office, the most consumed cooking oil in Lubuklinggau City is the Fortune brand. This phenomenon can lead to consumer loyalty in Lubuklinggau City to the oil. The research objectives are to analyze the level of satisfaction; level of consumer loyalty; direct effect of product quality, promotion and price on Fortune cooking oil consumer satisfaction; analyze the direct effect of product quality, promotion and price on Fortune cooking oil consumer loyalty; analyze the direct effect of consumer satisfaction on Fortune cooking oil consumer loyalty; analyze the effect of product quality, price and promotion on consumer loyalty through Fortune cooking oil consumer satisfaction. Data analysis using descriptive methods and SEM PLS analysis. The results obtained are 1) The level of household consumer satisfaction with Fortune cooking oil is very satisfied. 2) The level of consumer loyalty to Fortune cooking oil is very loyal. 3) Product quality, promotion and price have a positive and significant effect on Fortune cooking oil consumers. 4) Product quality, promotion and price have a positive and significant effect on Fortune cooking oil consumer loyalty. 5) Customer satisfaction has a positive and significant effect on Fortune cooking oil consumer loyalty. 6) Product quality, price and promotion have a positive and significant effect on consumer loyalty through customer satisfaction.